2021
DOI: 10.2463/mrms.mp.2019-0193
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Combination of Features on Gadoxetate Disodium-enhanced MR Imaging for Non-invasive Differential Diagnosis of Hepatocellular Carcinoma: The JAMP-HCC Study

Abstract: Purpose:To determine the optimal combination of gadoxetate disodium-enhanced magnetic resonance imaging (MRI) findings for the diagnosis of hepatocellular carcinoma (HCC) and to compare its diagnostic ability to that of dynamic computed tomography (CT) in patients with chronic liver disease. Methods:This multi-institutional study consisted of two parts: Study 1, a retrospective study to determine the optimal combination of gadoxetate disodium-enhanced MRI findings (decision tree and logistic model) to distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Currently, gadoxetic acid is used almost exclusively for liver MRI examinations in daily clinical practice in Japan because of its high performance in lesion detection and characterization. 4,[16][17][18] Traditionally, sensitivity is important in Japan because the Japan Society of Hepatology (JSH) guideline recommends liver resection or locoregional therapy based on early detection of HCC. 19 However, in the United States and Europe, liver transplantation is an important treatment option; thus, specificity is important.…”
Section: Detection Of Focal Liver Lesionsmentioning
confidence: 99%
“…Currently, gadoxetic acid is used almost exclusively for liver MRI examinations in daily clinical practice in Japan because of its high performance in lesion detection and characterization. 4,[16][17][18] Traditionally, sensitivity is important in Japan because the Japan Society of Hepatology (JSH) guideline recommends liver resection or locoregional therapy based on early detection of HCC. 19 However, in the United States and Europe, liver transplantation is an important treatment option; thus, specificity is important.…”
Section: Detection Of Focal Liver Lesionsmentioning
confidence: 99%
“…Gadoxetate disodium is a liver-specific contrast agent that is widely used in liver MRI because of its high performance in lesion detection and characterization. [1][2][3][4][5] However, several studies have reported that transient respiratory motion artifacts or truncation artifacts in the arterial phase (AP) can be observed more frequently in dynamic contrast-enhanced MRI (DCE-MRI) with gadoxetate disodium than that with extracellular contrast agents, [6][7][8] resulting in nondiagnostic image quality in the AP. DCE-MRI of the liver is typically performed using a breath-holding 3D gradient echo sequence (e.g., liver acquisition with volume acceleration, LAVA) with > 15 s of breathholding.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, gadoxetate disodium has become widely used for liver MRI in daily clinical practice because of its high performance in lesion detection and characterization. [18][19][20] However, few studies have discussed the imaging features of HLM on MRI. 10,[21][22][23] Our aim was to assess that gadoxetate disodium-enhanced MRI can be useful for distinguishing HCC from HLM because of this modality's multiparametric techniques, including chemical shift imaging, T2-weighted images (T2WI), DWI, dynamic study, and HBP.…”
Section: Introductionmentioning
confidence: 99%